Aerodynamic Research of the Experimental Prototype of the Variable Geometry Wind Turbine - Urbahs, Aleksandrs; Urbaha, Margarita; Carjova, Kristīne (Transport and aerospace engineering, 2017)
The aim of this research is to develop a vertical rotation axis variable geometry wind turbine (WT). The experimental prototype is being manufactured with the help of CAM (Computer-aided manufacturing) technologies – computer-based preparation of the product manufacturing process. The Institute of Aeronautics of Riga Technical University is using CNC (Computer Numerical Control) machines for manufacturing the innovative WT and its components. The aerodynamic research has been done in T-4 wind tunnel at an air flow rate from 5 m/s to 30 m/s. The power increase of the variable geometry WT is a topical issue. Installation of such WTs in wind farms is possible and is subject to further research.